X=4. Divide both side by -6 to get x by itself
Answer:
![\fbox{y = 8/5 }](https://tex.z-dn.net/?f=%20%5Cfbox%7By%20%3D%208%2F5%20%7D%20)
Explanation:
[to solve for y, first use the properties of equality to simplify the equation]
5y + 3 = 8y − 5 + 2y
5y + 3 = (8y + 2y) – 5
[regroup the like terms of y together: commutative property of equality ; adding in a different order will still give you the same result]
5y + 3 = 10y – 5
[combine like terms]
5y + 3 = 10y – 5
![\: \: \: \: \: \: -3 \: \: \: \: \: \: \: \: \: \: \: -3](https://tex.z-dn.net/?f=%20%5C%3A%20%5C%3A%20%5C%3A%20%5C%3A%20%5C%3A%20%5C%3A%20-3%20%5C%3A%20%5C%3A%20%5C%3A%20%5C%3A%20%5C%3A%20%5C%3A%20%5C%3A%20%5C%3A%20%5C%3A%20%5C%3A%20%5C%3A%20-3)
[subtract 3 from both sides in order to eliminate the constant term on the left side: subtraction property of equality]
5y = 10y – 8
–10y –10y
[subtract 10 from both sides in order to eliminate the variable term: subtraction property of equality]
-5y = -8
÷(-5) ÷(-5)
[divide both sides by -5 to cancel out the coefficient of y: division property of equality]
y = 8/5
Answer:
<h2>
k = 3</h2>
Step-by-step explanation:
The vertex is (d, e)
for quadratic function: f(x) = ax² + bx + c we have:
d = -b/a and d = (x₁ + x₂)/2
a = 1, b = k, x₁ = -4, x₂=-2
so:
d = -b/a = -k/1 = -k and d = (x₁ + x₂)/2 = (-4-2)/2 = -3
-k = -3
k = 3
Answer:
7/15
Step-by-step explanation:
turn 2/5 to have 15 as the denominator (6/15)
then do 13/15-6/15
answer is 7/15
Answer:
10.2 cm²
Step-by-step explanation:
The area (A) of a regular hexagon is
A =
× perimeter × apothem
Perimeter = 6 × 2 = 12 cm ( hexagon has 6 sides ), hence
A = 0.5 × 12 × 1.7 = 6 × 1.7 = 10.2 cm²